Sams teach yourself Microsoft Access 2000 programming in 24 hours - Kimmel, Paul. (Sams, 2000)
Sams Teach Yourself Access 2000 Programming in 24 Hours considerably improves the quality of the database applications that you can create with Microsoft Access. Upon completed this book, you will be able to understand any sample VBA code that you see, and possess the skills to attack all of the most common Access programming tasks. Topics covered include using data aware controls, creating data aware Web pages, creating views to organize data, building reusable code modules, programming reports, communicating results with graphing, automating contact and task management with Outlook, and Access programming for Internet Explorer